Gambaran Karakteristik Pasien HIV/AIDS: Tinjauan Retrospektif 2 Tahun Klinik VCT di Kabupaten Lombok Timur, Provinsi Nusa Tenggara Barat Tahun 2025 - Lalu Alfian Zartadi; Muthia Cenderadewi (Malahayati Nursing Journal, 2026)
ABSTRACT Voluntary Counseling and Testing (VCT) clinics play a critical role in HIV/AIDS control by providing counseling, early detection, and referral for treatment services. Understanding the characteristics of HIV/AIDS patients who access VCT services is essential to identify at-risk populations. This study aimed to examine the characteristics of HIV/AIDS patients attending a VCT clinic in East Lombok Regency, West Nusa Tenggara. This study employed a retrospective descriptive design using medical records of all HIV/AIDS patients who visited the VCT clinic at Dr. R. Soedjono Selong Regional General Hospital from January 2023 to December 2024. The variables included age, sex, occupation, referral source, and risk factors. Descriptive data analysis was conducted using Jamovi software. A total of 157 HIV/AIDS patients accessed VCT services during the 2023–2024 period, with 75 patients recorded in 2023 and 82 in 2024. The majority were male (77%), aged 31–40 years (38%), unmarried (59%), self-employed (73%), and men who have sex with men (MSM) (55%). Most patients were referred from primary health centers (69%). Between 2023 and 2024, the proportion of unmarried patients increased from 38.7% to 43.9%, MSM from 49% to 60%, and hospital referrals decreased from 21% to 3%. The proportion of self-employed patients declined from 81.3% to 65.9%. New occupational categories emerged in 2024, including teachers (4%) and students (5%). The majority of HIV/AIDS patients attending the VCT clinic at Dr. R. Soedjono Selong Hospital were males of productive age with high-risk behaviors. These findings highlight the need to strengthen early detection and targeted education, particularly among high-risk groups. Keywords: Characteristics, HIV/AIDS, VCT Clinic, East Lombok Regency, West Nusa Tenggara Province.  ABSTRAK Klinik Voluntary Counseling and Testing (VCT) berperan penting dalam upaya penanggulangan HIV/AIDS dengan menyediakan layanan konseling, deteksi dini, dan rujukan pengobatan. Memahami karakteristik pasien HIV/AIDS yang mengakses klinik VCT penting untuk mengidentifikasi populasi berisiko. Penelitian ini bertujuan untuk mengetahui karakteristik pasien HIV/AIDS pada Klinic VCT di Kabupaten Lombok Timur Nusa Tenggara Barat. Penelitian ini merupakan penelitian deskriptif retrospektif dengan menggunakan rekam medis seluruh pasien HIV/AIDS yang mengunjungi klinik VCT di RSUD Dr. R. Soedjono Selong periode Januari 2023 hingga Desember 2024. Variabel yang digunakan meliputi usia, jenis kelamin, pekerjaan, sumber rujukan, dan faktor risiko. Analisis data deskriptif dilakukan menggunakan perangkat lunak Jamovi. Hasil: Sebanyak 157 pasien HIV/AIDS mengakses layanan VCT selama periode 2023–2024, dengan 75 pasien pada tahun 2020 dan 82 pada tahun 2024. Proporsi terbesar adalah laki-laki (77%), berusia 31–40 tahun (38%), belum menikah (59%), wiraswasta (73%), dan laki-laki yang berhubungan seks dengan laki-laki (55%), serta berasal dari rujukan puskesmas (69%). Antara tahun 2023 dan 2024, proporsi pasien belum menikah meningkat dari 38,7% menjadi 43,9%, LSL meningkat dari 49% menjadi 60%, rujukan ke rumah sakit dari 21% menjadi 3%, dan wiraswasta menurun dari 81,3% menjadi 65,9%. Kategori baru, yaitu guru (4%) dan siswa (5%), akan mengakses layanan VCT pada tahun 2024. Mayoritas pasien HIV/AIDS di Klinik VCT RSUD Dr. R. Soedjono Selong adalah laki-laki usia produktif dengan perilaku berisiko. Temuan ini menggarisbawahi perlunya peningkatan deteksi dini dan edukasi, terutama bagi kelompok berisiko. Kata Kunci: Karakteristik, HIV/AIDS, Klinik VCT di Kabupaten Lombok Timur, Provinsi Nusa Tenggara Barat.